Answer:
No, h = (-23)/5
Explanation:
Solve for h:
3 (4 - 6 h) - 7 h = 127
3 (4 - 6 h) = 12 - 18 h:
12 - 18 h - 7 h = 127
-18 h - 7 h = -25 h:
-25 h + 12 = 127
Subtract 12 from both sides:
(12 - 12) - 25 h = 127 - 12
12 - 12 = 0:
-25 h = 127 - 12
127 - 12 = 115:
-25 h = 115
Divide both sides of -25 h = 115 by -25:
(-25 h)/(-25) = 115/(-25)
(-25)/(-25) = 1:
h = 115/(-25)
The gcd of 115 and -25 is 5, so 115/(-25) = (5×23)/(5 (-5)) = 5/5×23/(-5) = 23/(-5):
h = 23/(-5)
Multiply numerator and denominator of 23/(-5) by -1:
Answer: h = (-23)/5